Penyelesaian Kerugian Keuangan Negara - Bambang Wahyudi (Centre for Public Policy and Management Studies, 2008)
Every misuse in public finance which leads to financial lost can be treated with three kinds of sanctions i.e. criminal sanction, administrative sanction and to substitute the financial lost (financial sanction). The process of these three sanctions must be done at the same time. If not, it may become expired and the sanctions cannot be implemented.Keywords: public finance lost, responsibility, punishment related to public financial lost